2017
DOI: 10.1515/helm-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Windstorms as mediator of soil nematode community changes: Evidence from European spruce forest

Abstract: SummaryNematode communities in a Norway spruce forest in High Tatra National Park, Slovakia were monitored for the period of several years (2006 and 2013). Unfortunately, in May 2014 natural windstorm damaged the forest. This disastrous event, together with preliminary obtained results allowed us to compare the direct impact of windstorm damage of forest habitat on soil nematode assemblages. The forest destruction by windstorm had a signifi cant effect on the total nematode abundance, the abundance of omnivore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…These findings support our hypothesis that biological diversity would be lowest in the agricultural soils due to periodic perturbation, land management, and crop monoculturing, consistent with the results by Neher et al, (2005); even though AGR had the highest overall nematode abundance, likely due the periodic organic manure inputs (Hu et al, 2018). Bacterivorous nematodes are often the most dominant feeding group in forest (Neher et al, 2005;Yeates, 2007;Renčo & Čerevková, 2017) and agricultural (Neher et al, 2005, Renčo et al, 2010 soils. The preponderance of Ba 2 bacterivores (A. nanus, C. persegnis, and C. propinquus) in all ecosystems in our study was likely due to the high microbial biomasses in FOR and MEA and to the management (tillage and fertilisation) in the corn monoculture in AGR.…”
Section: Relationships Of Ecosystem Type With Soil Properties and Nemsupporting
confidence: 86%
“…These findings support our hypothesis that biological diversity would be lowest in the agricultural soils due to periodic perturbation, land management, and crop monoculturing, consistent with the results by Neher et al, (2005); even though AGR had the highest overall nematode abundance, likely due the periodic organic manure inputs (Hu et al, 2018). Bacterivorous nematodes are often the most dominant feeding group in forest (Neher et al, 2005;Yeates, 2007;Renčo & Čerevková, 2017) and agricultural (Neher et al, 2005, Renčo et al, 2010 soils. The preponderance of Ba 2 bacterivores (A. nanus, C. persegnis, and C. propinquus) in all ecosystems in our study was likely due to the high microbial biomasses in FOR and MEA and to the management (tillage and fertilisation) in the corn monoculture in AGR.…”
Section: Relationships Of Ecosystem Type With Soil Properties and Nemsupporting
confidence: 86%
“…These changes were likely determined by the sustained nutrient enrichment produced by defoliated and dead trees, which increased the abundance of opportunistic nematodes in the lower c‐p groups (supported by the higher values of the enrichment index under those trees). Previous studies have reported similar trends in the modification of the values of these indices associated to disturbances such as windstorms (Renčo & Čerevková, ), floodings (Wagner, Eisenhauer, & Cesarz, ), experimental warming (Thakur et al., ), or fires (Pen‐Mouratov, He, & Steinberger, ). Functionally, lower values of the maturity index and higher values of the plant parasitic and enrichment indices frequently reflect a high microbial abundance and activity that translate into faster N mineralization and soil respiration rates (Bongers & Bongers, ; Ferris & Matute, ).…”
Section: Discussionsupporting
confidence: 58%
“…The dying-off process in mountain spruce forests was caused by several biotic (bark beetles) and non-biotic factors (air pollution), forming a cause-and-effect chain that reinforced the disease process, resulting in a total annihilation of the stand over an extended period of time [81][82][83]. Air pollution, prolonged summer droughts in the years 2003-04 and 2006-07, and the catastrophic hurricane of 2004 resulted in the weakening of spruce stands in the montane zone [84,85]. Bark beetles attacked the weakened trees as part of a large-scale infestation which affected a considerable forest area in the Silesian Beskids within a short time [86].…”
Section: Discussionmentioning
confidence: 99%